Calculate 81406
Calculate the equation and do the test.
(x+6)/2 - (x+4)/4 = (2x+1)/3 – (x-4)/6
(x+6)/2 - (x+4)/4 = (2x+1)/3 – (x-4)/6
Correct answer:
![](/img/6/numbers_1.webp)
Tips for related online calculators
Need help calculating sum, simplifying, or multiplying fractions? Try our fraction calculator.
Do you have a linear equation or system of equations and are looking for its solution? Or do you have a quadratic equation?
Do you have a linear equation or system of equations and are looking for its solution? Or do you have a quadratic equation?
You need to know the following knowledge to solve this word math problem:
Grade of the word problem:
Related math problems and questions:
- Calculate 4089
Calculate and perform the test. 3a / 2 + 5/6 = a / 3 - 3/2
- Equation 4293
Solve the equation and perform the test: 2 (4x + 3) - 2 = 6 - 5 (1 - x)
- Equations 4648
Solve the system of equations by any method and perform the test: 2 (x + y) -3 (y + 2) = -1 x + 2 / 3y-6 = 2
- Equation 4055
Solve the equation and perform the test: a) 3 (5-2x) + 5x = 5 -3 (x -1) b) 2 (4y + 3) -3 = 2 - 5 (1 - y)
- Equation 4300
Solve the equation and perform the test: 1- (x-x/7-1/7) = 7-9x/2 +5/2
- Please
Please determine the solvability conditions of the equation, solve the equation and perform the test: x divided by x squared minus 2x plus1 the whole minus x + 3 divided by x squared minus one is equal to 0: x/(x²-2x+1) - (x+3)/( x²-1) = 0
- Inequality: 3538
Example1: Solve a linear equation and perform a test: 6x- (3x + 2) = x-8 Example 2: Solve a linear inequality: 3y + 2 * (y + 1) ≥2y-7